The outer limits of European Union law - Barnard, Catherine; Odudu, Okeoghene, 1976- (Hart Pub., 2009)
By considering general themes (legitimacy) and core subject areas (policing, free movement of goods, remedies), this book reveals the various techniques used by the Court of Justice, Community institutions and Member States to define and modify the outer limits of the European Union and European Union Law.